Variation in inpatient allied health service provision in Australian and New Zealand hospitals. (3rd August 2021) - Jepson, Megan; Sarkies, Mitchell; Haines, Terry; ,
Abstract: Objective: To describe the variability of allied health services on weekends, relative to weekdays, throughout Australian and New Zealand hospitals. Methods: A prospective, cross‐sectional observational study embedded within a cluster randomised control trial. Allied health managers provided administrative data relating to allied health service events. Results: In one month, there were a total of 243 549 allied health service events recorded from 91 sampled hospitals. The mean difference between weekday and weekend allied health service events (daily, per ward) for physiotherapy was 6.52 (95% CI 5.65 to 7.40), acute wards 12.03 (95% CI 10.25 to 13.82) and for metropolitan hospitals 14.47 (95% CI 12.22 to 16.73), revealing more allied health service events of longer duration on weekdays compared to weekends. Conclusions: This research is the first of its kind to describe variation in allied health service provision and potential research to practice gaps across weekday and weekend days in various inpatient settings.